Album from My Summer Seminar in Israel - Harders, Marian (The Biblical archaeology review, 1983)
I was one of a group of 16 people who participated in BAR’s Israel seminar this past summer—a stimulating, invigorating (and slenderizing) six-week exploration of the Holy Land. There was more to the adventure than trying to absorb an overwhelming amount of Biblical archaeology and geography; I also added a new cultural awareness to […]